ANALISIS PERENCANAAN KOMUNIKASI DALAM MENYUSUN DETAIL ENGINEERING DESIGN (DED) INFRASTRUKTUR KAWASAN RUMAH SEDERHANA SEHAT (RSH) KOTA BANJARMASIN TAHUN 2014 - H.Aqil Rachmatullah; Nina Widiyawati; Deli Anhar (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2014)
The research was based on the rationale for the development of communication plans drafting Detail Engineering Design (DED), so as to increase the role of planning consultants assisted the relevant agencies in the province of South Kalimantan in order to maximize the role of Detail Engineering Design (DED) in the construction of residential areas in the city of Banjarmasin in South Kalimantan Province .Issues to be discussed in this study focuses on the question:1. What is the purpose of communication planning in preparing Detail Engineering Design (DED) Region Infrastructure Simple Healthy House City of Banjarmasin in 2014?2. How phases - planning stages of communication in compiling Detail Engineering Design (DED) Region Infrastructure Simple Healthy House City of Banjarmasin in 2014?3. Anyone who is involved in the planning of communication in compiling Detail Engineering Design (DED) Region Infrastructure Simple Healthy House (RSH) City of Banjarmasin in 2014?The research results indicate that communication planning Detail Engineering Design (DED) Region Infrastructure Simple Healthy House City of Banjarmasin in the category type top-down planning and bottom up. Types can be seen from the bottom up and the authorities are planning major initiatives in the Office of institutions lower regional work units deconcentration Kemenpera scope, type of top down where South Kalimantan Province and the Ministry of Housing to support the plan. Keywords: Communication Planning Detail Engineering Design, Housing